Proceedings of the 2013 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining 2013
DOI: 10.1145/2492517.2492613
|View full text |Cite
|
Sign up to set email alerts
|

Semantically meaningful group detection within sub-communities of Twitter blogosphere

Abstract: This paper addresses the problem of semantically meaningful group detection within a sub-community of twitter micro-bloggers by utilizing a topic modeling, multi-objective clustering approach. The proposed group detection method is anchored on the Latent Dirichlet Allocation (LDA) topic modeling technique, aiming at identifying clusters of twitter users that are optimal in terms of both spatial and topical compactness. Specifically, the group detection problem is formulated as a multiobjective optimization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The results demonstrated the superiority of the ACA as a feature selector among other algorithms. Several studies showed the application of the LDA method as a feature extractor in text categorization using the GA in the feature selection stage (Chen et al, 2017;Panichella et al, 2013;Sotiropoulos et al, 2014;Sotiropoulos et al, 2016). The clustering problem was reformulated by Sotiropoulos et al (2016) as a discrete optimization problem within the n-dimensional standard simplex.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated the superiority of the ACA as a feature selector among other algorithms. Several studies showed the application of the LDA method as a feature extractor in text categorization using the GA in the feature selection stage (Chen et al, 2017;Panichella et al, 2013;Sotiropoulos et al, 2014;Sotiropoulos et al, 2016). The clustering problem was reformulated by Sotiropoulos et al (2016) as a discrete optimization problem within the n-dimensional standard simplex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results demonstrated that LDA-GA can determine robust LDA configurations. Sotiropoulos et al (2014) proposed a group detection method within a subcommunity of Twitter micro-bloggers by utilizing a topic modeling. They utilized the LDA topic modeling technique to identify clusters of Twitter users considering both spatial and topical compactness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cao et al [20] proposed a K-Means algorithm based on the similarity of Mashup services to cluster services by combining the description document and the corresponding tags of Mashup services. Sotiropoulos et al [15] presented a service clustering model based on topic probability and domain characteristics. Shi et al [16] provided an enhanced-LDA service clustering method based on word vectors to cluster all the words in the Web service description document, and to take these words clustering information into the training process of the LDA model.…”
Section: Related Workmentioning
confidence: 99%
“…The purity of each C i and the mean purity of all Web service classification in EWSC are respectively defined in the formulas ( 13) and (14). Similarly, the entropy of each C i and the mean entropy of all Web service categories in EWSC are respectively defined in the formulas (15) and (16).…”
Section: B Evaluation Metricsmentioning
confidence: 99%